(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
This write-up postulates that integration of Artificial Intelligence (AI) offers transformative potential for Nepal’s hospitality and tourism industry, enhancing visitor experiences, improving operational efficiency, and supporting sustainable development. AI-driven tools-such as chatbots, real-time language translation, and predictive analytics-can streamline service delivery while safeguarding the nation’s cultural authenticity and human-centred approach to hospitality. Advanced technologies like virtual reality (VR), augmented reality(AR), and biometric systems further enhance tourist engagement, safety, and decision making. Importantly, AI is not a replacement for human roles but a collaborative force that empowers workers to deliver more personalised and emotionally intelligent services. This synergy between innovation and tradition positions Nepal as a promising leader in AI-augmented tourism. With strategic implementation, Nepal can strengthen its global tourism competitiveness while preserving its unique cultural heritage and values.